Development of Functional Healthy Korea Traditional Soondae with Addition of Organic Farming Pumpkin Using Sensory Evaluation - Kyun, Young; ., Kim (International Journal of Engineering and Technology, 2018)
In this paper, in order to propose the standard cooking method of Soondae, which is one of most favorite traditional food sausage type Korea.Nowadays, obesity and cardiovascular diseases are changing food consumption habits; these changes have fostered the development of products with functional ingredients that meet the market demands for maintaining a healthy body. The people's interest to the healthy, Low-calories food is growing up, the Foodservice industry is developing and making Functional food, which helps to a sale strategy.In order to propose the standard cooking method of Soondae, which is one of most favorite traditional food sausage type Korea, In This study was to develop the Soondae with addition of organic farming pumpkin using sensory evaluation. The survey for the recognition and preference for Soondae using organic farming pumpkins performed from 15 to May 30 in the year of 2018 by subjecting 159 customer, and frequency analysis was used for the statistical technique. We analyzed the possible data by use of statistic program SPSS Windows 18.0 Version. Through the survey results, the organic farming pumpkin Soondae develop new products and recipes.Questionnaire investigation result for the group revealed that 60% or more of the group showed common level of their interest in the development of Pumpkin Soondae. Improved texture added pumpkin. Dietary fiber, crude protein of Pumpkin Soondae increased but crud fat and salinity of Pumpkin Soondae were decreased. Pumpkin Soondae functionality has been improved. Modern men, colorectal cancer, adult diseases, such as cardiovascular disease and increase as the increase of dietary fiber and carbohydrate reduction seem to have a very positive effect.Â Â